EXOPOLYSACCHARIDE PRODUCTION AND ITS BIOACTIVITIES OF THE EDIBLE PLEUROTUS OSTREATUS IN SUBMERGED CULTURE - IWAN SASKIAWAN (BIOTROPIA, 2009)
Submerged cultures were used to study the influence of  various carbon sources on the mycelial biomass and exopolysaccharide production of  Pleurotus  ostreatus. The antimicrobial and antioxidant activity of   the exopolysaccharide were also determined.   The yield of  mycelial biomass of  7.06 g/l, 5.12 g/l, 4.66 g/l, and 2.96 g/l was obtained by utilization of  maltose, glucose,  lactose  and  starch  as  a  carbon  source,  respectively.  Furthermore,  in  the medium containing maltose, lactose, glucose, and starch produce 100.05 mg/l, 97.73 mg/l, 78.63 mg/l, and 70.45 mg/l of  exopolysaccharide, respectively.  The assay of  antimicrobial and antioxidant activity showed that the exopolysaccharide is more active to inhibit the growth of  B. subtilis rather  than  those  of  E.  coli  and  S.  cerevisiae. Furthermore,  the  exopolysaccharide was  also indicated  to have antioxidant activity.Key words: Pleurotus ostreatus, exopolysaccharide, antimicrobial activity, antioxidant activity